TANGGUNG JAWAB DAN KEWENANGAN PPAT DALAM MEMBANTU PIHAK TERKAIT ATAS KELENGKAPAN ADMINISTRASI DAN PELAYANAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (STUDI KASUS: PUTUSAN MA NOMOR:46 PK/PID/2013) - JURIA BESTY PASARIBU (PREMISE LAW JURNAL, 2017)
BPHTB (Duty on Land and Building Right Acquisition) actually has to be payed by taxpayers; in reality, they entrust it to PPAT (official empowered to draw up land deeds) so that PPAT has to be responsible for it. It indicates that it is contrary to law. This thesis would discuss it. The problem is that PPAT entrusts it to another party that is not responsible for paying it. The research problems were as follows: how far the responsibility of PPAT for the BPTB safekeeping was and how far the responsibility of PPAT for the payment of BPHTB was when it was missing. A person who has no responsibility according to regulation or contract and he violates against law, PPAT who entrusts PPHTB can be imprisoned and can also be imposed a sanction of code of ethics since he violates PPAT Code of Ethics and it is related to writing certificate. Keywords: Self Assessment, Acquisition of Land and Building, taxpayer